First Case of Glyphosate Resistance in Bromus catharticus Vahl.: Examination of Endowing Resistance Mechanisms - Yanniccari, Marcos; Vázquez-García, José G.; Gómez-Lobato, María E.; Rojano-Delgado, Antonia M.; Alves, Pedro L. da C. A.; De Prado, Rafael (Frontiers in Plant Science, 2021)
Bromus catharticus Vahl. has been used as a valuable forage crop, but it has also been noted as a weed of winter crops and an invader in several countries. In Argentina, a putative glyphosate-resistant population of B. catharticus was identified as a consequence of the lack of effective control with glyphosate in the pre-sowing of wheat. Plant survival and shikimate accumulation analysis demonstrated a lower glyphosate-sensitivity of this population in comparison to a susceptible B. catharticus population. The resistant population was 4-fold more resistant to glyphosate than its susceptible counterpart. There was no evidence of target-site mechanisms of glyphosate resistance or an enhanced capacity to metabolise glyphosate in the resistant population. However, the resistant plants showed a lower foliar retention of glyphosate (138.34 µL solution g-1 dry weight versus 390.79 µL solution g-1 dry weight), a reduced absorption of 14C-glyphosate (54.18 % versus 73.56 %) and lower translocation of 14C-glyphosate from the labelled leaf (27.70 % versus 62.36 %). As a result, susceptible plants accumulated a 4.1-fold higher concentration of 14C-glyphosate in the roots compared to resistant plants. The current work describes the first worldwide case of glyphosate resistance in B. catharticus. A reduced foliar retention of herbicide, a differential rate of glyphosate entry into leaves and an altered glyphosate translocation pattern would be the most likely mechanisms of glyphosate exclusion.